Amino Acid Distributions at Oligomeric Membrane Protein Interfaces - Drechslerová, Anna (Jihočeská univerzita, 2021)
A set of twelve exemplary oligomeric transmembrane proteins was selected and subjected to an analysis in order to discover more information about their amino acid distribution. These findings were compared to an aquaporin dataset and evaluated with regard to protein and lipid interfaces.
Amino Acid Distributions at Oligomeric Membrane Protein Interfaces
Amino Acid Distributions at Oligomeric Membrane Protein Interfaces
Keywords: Oligomeric transmembrane proteins; aquaporins; amino acids; amino acid distribution; protein interface; lipid interface; membrane transport proteins; channel proteins; carrier proteins; bioinformatics; Oligomeric transmembrane proteins; aquaporins; amino acids; amino acid distribution; protein interface; lipid interface; membrane transport proteins; channel proteins; carrier proteins; bioinformatics